Three new osmiine bee species from the extreme desert of Saudi Arabia with specialized pollen-collecting behaviours (Megachilidae, Osmiini) - Müller, Andreas; Shebl, Mohamed A.; Alqarni, Abdulaziz S. (Zootaxa, 2026)
Three new osmiine bee species (Megachilidae, Osmiini) inhabiting the Arabian desert are described: Hoplitis (Hoplitis) heliotropii sp. nov. from Saudi Arabia, H. (Hoplitis) trichodesmae sp. nov. from Saudi Arabia and the Arava Valley in Israel, and H. (Platosmia) trisinuata sp. nov. from Saudi Arabia and Jordan. Field observations and microscopical analyses of female pollen loads indicate that all three species exhibit a pronounced preference for Boraginaceae as pollen hosts, i.e. H. heliotropii and H. trisinuata for Heliotropium and H. trichodesmae for Trichodesma. The females of H. heliotropii and H. trisinuata possess apically curved or hooked bristles on the proboscis and the fore legs, respectively, which they use to scrape pollen out of the narrow flower tubes of Heliotropium, whereas females of H. trichodesmae apply buzzing to shake pollen out of the flowers of Trichodesma. The occurrence of specialized pollen-collecting bristles used by Palaearctic bees and pollen wasps to exploit Heliotropium flowers and the buzzing behaviour in bees of the Megachilidae are discussed.